2014
DOI: 10.1371/journal.pone.0087371
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Oxidative Stress Increases Growth and Tumorigenic Potential of MCF-7 Breast Cancer Cells

Abstract: Accumulating evidence suggests that exposures to elevated levels of either endogenous estrogen or environmental estrogenic chemicals are associated with breast cancer development and progression. These natural or synthetic estrogens are known to produce reactive oxygen species (ROS) and increased ROS has been implicated in both cellular apoptosis and carcinogenesis. Though there are several studies on direct involvement of ROS in cellular apoptosis using short-term exposure model, there is no experimental evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 65 publications
3
85
0
2
Order By: Relevance
“…In the present study, adipose tissue HCB concentrations were negatively associated with ECadherin expression. It has been reported that chronic exposure to POPs increases the production of reactive oxygen species (ROS), inducing the growth and survival of MCF-7 breast cancer cells and downregulating E-Cadherin expression (Mahalingaiah and Singh, 2014). In vivo and in vitro experimental studies found that PCB-mediated ROS production would induce invasiveness and metastasis by activating Rho-Associated Kinase (ROCK) activity (Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, adipose tissue HCB concentrations were negatively associated with ECadherin expression. It has been reported that chronic exposure to POPs increases the production of reactive oxygen species (ROS), inducing the growth and survival of MCF-7 breast cancer cells and downregulating E-Cadherin expression (Mahalingaiah and Singh, 2014). In vivo and in vitro experimental studies found that PCB-mediated ROS production would induce invasiveness and metastasis by activating Rho-Associated Kinase (ROCK) activity (Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent exposure to ROS (chronic oxidative stress) renders cancer cells physiologically adapted to ROS, thus facilitating increased survival (Mahalingaiah and Singh, 2014) through upregulation of Survivin, which abolishes the G2/M checkpoint and allows cells to progress through mitosis (Li et al, 1998). Owing to its antiapoptotic function, Survivin inhibits radiotherapy-and chemotherapy-induced cell death, thus resulting in tumor progression and drug resistance (Zaffaroni and Daidone, 2002;Schlette et al, 2004;Rödel et al, 2005;Fuessel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, activation of nuclear factor kB has also been shown to be involved in chemotherapeutic resistance through various mechanisms, such as through upregulation of multidrug resistance (MDR) genes (Thévenod et al, 2000), increased expression of Bcl-2 (Viatour et al, 2003), and increased angiogenic vascular endothelial growth factor (Morais et al, 2009). Adaptation to chronic oxidative stress has been shown not only to increase the growth of cancer cells but also to affect directly the response to chemotherapy, as many anticancer drugs exert their cytotoxicity by generating ROS (Spitz et al, 1993;Scheltema et al, 2001;Mahalingaiah and Singh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that continued oxidative stress leads not only to increased cell survival, but also increased tumorigenic potential of cancer cells (6,7). Oxidative stress contributes to the expansion of genomic instability throughout the genome, and subsequent gene mutations involved in the initiation of tumorigenesis (15).…”
Section: Iron-induced Dna Damage In Endometriosis and Endometriosis-amentioning
confidence: 99%
“…Endometriosis also possesses a malignant transformation potential to ovarian carcinoma. Recently, several studies have indicated that heme and iron, present in endometriotic cysts, damage the endometriotic cells by inducing inflammation and oxidative stress (3)(4)(5)(6)(7). Simultaneously, several genes associated with acute antioxidant response, DNA damage repair and cell cycle modulation are activated.…”
Section: Introductionmentioning
confidence: 99%